2013
DOI: 10.1016/j.molcel.2013.03.026
|View full text |Cite
|
Sign up to set email alerts
|

An ORC/Cdc6/MCM2-7 Complex Is Formed in a Multistep Reaction to Serve as a Platform for MCM Double-Hexamer Assembly

Abstract: In Saccharomyces cerevisiae and higher eukaryotes, the loading of the replicative helicase MCM2-7 onto DNA requires the combined activities of ORC, Cdc6, and Cdt1. These proteins load MCM2-7 in an unknown way into a double hexamer around DNA. Here we show that MCM2-7 recruitment by ORC/Cdc6 is blocked by an autoinhibitory domain in the C terminus of Mcm6. Interestingly, Cdt1 can overcome this inhibitory activity, and consequently the Cdt1-MCM2-7 complex activates ORC/Cdc6 ATP-hydrolysis to promote helicase loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
183
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(198 citation statements)
references
References 32 publications
13
183
1
1
Order By: Relevance
“…Of interest, it was recently shown that loading of the first MCM2-7 hexamer onto DNA occurrs within seconds, whereas the subsequent formation of a MCM2-7 double hexamer is slow and takes several minutes. 35 Consistently, we show here that about 10% of Cdc6-YFP was immobilized on chromatin for more than a minute during telophase suggesting that its engagement in loading MCM2-7 onto replication origins is a time-consuming process.…”
Section: Discussionsupporting
confidence: 86%
“…Of interest, it was recently shown that loading of the first MCM2-7 hexamer onto DNA occurrs within seconds, whereas the subsequent formation of a MCM2-7 double hexamer is slow and takes several minutes. 35 Consistently, we show here that about 10% of Cdc6-YFP was immobilized on chromatin for more than a minute during telophase suggesting that its engagement in loading MCM2-7 onto replication origins is a time-consuming process.…”
Section: Discussionsupporting
confidence: 86%
“…The purified Mcm2-7 hexamer can hydrolyze ATP in vitro (Schwacha and Bell 2001;Ilves et al 2010;Fernandez-Cid et al 2013), but the active form of the helicase, when Mcm2-7 is part of a CMG complex, has a significantly higher ATPase activity (Ilves et al 2010). On the other hand, the ATPase rate of the Mcm2-7 double hexamer is not known.…”
Section: Segmentation and Subunit Assignment Of The 3d Em Map Of The mentioning
confidence: 99%
“…Mcm2-7 double-hexamer formation is a multistep reaction during which two Mcm2-7 hexamers are recruited one after another to replication origins Fernandez-Cid et al 2013;Frigola et al 2013). In S. cerevisiae, Ó 2014 Sun et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml).…”
mentioning
confidence: 99%
See 2 more Smart Citations